Effects of a short school-based vaping prevention program for high school students - Devin M. McCauley; Michael Baiocchi; Summer Cruse; Bonnie Halpern-Felsher (Preventive Medicine Reports, 2023)
Educational programs that address adolescents’ misperceptions of e-cigarette harms and benefits and increase refusal skills play an important role in preventing initiation and use. This study evaluates changes in adolescents’ e-cigarette perceptions, knowledge, refusal skills, and intentions to use following a real-world implementation of a school-based vaping-prevention curriculum. Study participants were 357 9th-12th grade students from one high school in Kentucky, United States who participated in a 60-minute vaping prevention curriculum from the Stanford REACH Lab’s Tobacco Prevention Toolkit. Participants completed pre- and post-program assessments regarding their e-cigarette knowledge, perceptions, refusal skills, and intentions to use e-cigarettes. Matched paired t-tests and McNemar tests of paired proportions were applied to assess changes in study outcomes. Following the curriculum, participants indicated statistically significant changes on all 15 survey items related to e-cigarette perceptions (p’s < 0.05). Participants demonstrated improved knowledge that e-cigarettes deliver nicotine in the form of an aerosol (p <.001), reported that if a friend offered them a vape it would be easier to say no (p <.001), and indicated they would be less likely to take the vape (p <.001) after receiving the curriculum. Other survey items related to knowledge, refusal skills, and intentions did not demonstrate significant changes. Overall, participation in a single session vaping-prevention curriculum was associated with several positive changes in high school students’ e-cigarettes knowledge, perceptions, refusal skills, and intentions. Future evaluations should examine how such changes affect long-term trajectories of e-cigarette use.